Preparing A Vacant Possession for M1 MSN Development Sdn. Bhd. / Nur Ain Darwisyah Mohd Saufi - Mohd Saufi, Nur Ain Darwisyah (Universiti Teknologi MARA UiTM,Perak, 2022)
The practical report titled “Preparing a Vacant Possession for M1 MSN Development Sdn. Bhd.” covers the complete operation of Building Condition Assessment (BCA). The aim of this report is to prepare a report for developer about all the defect has been found in the house and submit to the contractor to make repair work. The main objective is to identify how to conduct an inspection for vacant possession and collect more detail of all the defects that has been found in the house. On the site, all the defects have been recorded and put a defect tagging on the house and take measurements internal and external of the house. To conclude, it is important to do an inspection for vacant possession to ensure that buyer feel satisfied and safety to occupy the house purchased.